The Impact Of Board Structure On Performance. A Case Study Of Selected Rural Banks In Ashanti Region - ERNEST, OSEI (KNUST, 2025)
A Thesis Submitted to the Department of Accounting and Finance, In Partial Fulfillment of the Requirement for the Degree Of Master of Business Administration (Accounting -Option).